High Affinity Aptamers and Their Specificity for Azaspiracid-2 Using Capture-SELEX - Jiaping Yang; Xinhao Li; Weiqin Sun; Yunyi Cui; Han Chen; Yao Yang; Mingjuan Sun; Lianghua Wang (Marine Drugs)
Azaspiracids are a type of polyether toxin. Currently, the existing detection methods for azaspiracids all have certain drawbacks. Aptamers offer a cost-effective and convenient approach for the detection of azaspiracids. By employing the Capture-SELEX (Systematic evolution of ligands by exponential enrichment) method to screen aptamers specific to azaspiracid-2, a high-affinity aptamer can be identified for toxin detection. The bin ding affinity of the toxin is verified using biolayer interferometry (BLI) technology. Additionally, computer simulations are utilized to explore the binding sites of the aptamer and conduct molecular dynamics simulations to investigate the stability of the aptamer–toxin complex. Further optimization of the obtained aptamers is carried out to enhance their affinity for the toxin. Ultimately, two aptamers, JD2-RM3-27C28T and JD3-RMM1, are obtained, with dissociation constants (KD) improved by two orders of magnitude (KD = 8.7 × 10⁻⁸ M and KD = 6.8 × 10⁻⁸ M, respectively). These aptamers have the advantage of being incorporated into a new AZA2 assay that is more accurate and ethical than biological monitoring methods, and more economical than LC-MS. In the future, this is expected to demonstrate significant advantages in the fields of food safety, environmental toxin monitoring, toxin exposure diagnosis, and public health monitoring.